Pengaruh Kualitas Kehidupan Kerja dan Kepemimpinan yang Melayani Terhadap Kinerja dengan Organizationalcitizenship Behavior (OCB) Sebagai Mediasi - Adi Arianto; Endang Tjahjaningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the influence of quality of work life and servant leadership on ASN performance, with Organizational Citizenship Behavior (OCB) as a mediating variable. This study was conducted on the State Civil Apparatus (ASN) in Tegal City, with a population of 2,500 people. The research sample was 104 ASN selected using purposive sampling technique. Data collection was carried out through questionnaires, and data analysis used the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The research results show that the quality of work life and servant leadership have a positive and significant effect on OCB. Furthermore, OCB has a positive and significant effect on ASN performance. In addition, OCB has been proven to mediate the influence of quality of work life and servant leadership on ASN performance. These findings indicate that improving the quality of work life and implementing servant leadership can increase ASN extra-role behavior, which ultimately contributes to increased performance. The implications of this research highlight the importance of improving the work environment and a service-oriented leadership style to improve ASN performance through strengthening OCB. These results can be a basis for policy makers in designing strategies to increase the effectiveness and productivity of ASN in Tegal City.